2019
DOI: 10.1016/j.bpj.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Hemagglutinin Modulates Phosphatidylinositol 4,5-Bisphosphate Membrane Clustering

Abstract: The lipid phosphatidylinositol 4,5-bisphosphate (PIP2) forms nanoscopic clusters in cell plasma membranes; however, the processes determining PIP2 mobility and thus its spatial patterns are not fully understood. Using super-resolution imaging of living cells, we find that PIP2 is tightly colocalized with and modulated by overexpression of the influenza viral protein hemagglutinin (HA). Within and near clusters, HA and PIP2 follow a similar spatial dependence, which can be described by an HA-dependent potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 85 publications
3
79
0
Order By: Relevance
“…Whether M2 ALPS and M2 Epsin are enriched at the viral budding site cannot be concluded from our data. Note, however, that the ␣0-helix of Epsin binds to PtdIns(4,5)P2 even outside the ETNH domain and that HA also colocalizes with PtdIns(4,5)P2 (65). Thus, the proposed mutual affinity of HA and M2 Epsin for this negatively charged lipid present only at the inner leaflet of the plasma membrane might cause their colocalization.…”
Section: Discussionmentioning
confidence: 97%
“…Whether M2 ALPS and M2 Epsin are enriched at the viral budding site cannot be concluded from our data. Note, however, that the ␣0-helix of Epsin binds to PtdIns(4,5)P2 even outside the ETNH domain and that HA also colocalizes with PtdIns(4,5)P2 (65). Thus, the proposed mutual affinity of HA and M2 Epsin for this negatively charged lipid present only at the inner leaflet of the plasma membrane might cause their colocalization.…”
Section: Discussionmentioning
confidence: 97%
“…Whether M2 ALPS and M2 Epsin are enriched at the viral budding site cannot be concluded from our data. Note, however, that the α0-helix of Epsin binds to PtdIns(4, 5)P2 even outside of the ETNH-domain and that HA also co-localizes with PtdIns(4, 5)P2 (65). Thus, the proposed mutual affinity of HA and M2 Epsin for this negatively charged lipid present only at the inner leaflet of the plasma membrane might cause their co-localization.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of the second late domain motif PPRY also reduces virus shedding, with the majority of particles remaining outside intracellular vesicles rather than inside for the WT BTV particles [ 50 ]. Another striking similarity between BTV and enveloped virus maturation is the involvement of the lipid phosphatidylinositol (4,5) bisphosphate (PI(4,5)P2), which is a key effector of virus release [ 51 , 52 ]. It has been reported that PI(4,5)P2 co-localises with NS3 and VP5, and that depletion of this lipid reduced BTV maturation and release [ 53 ].…”
Section: The Membrane Protein Ns3 Is Responsible For Trafficking Amentioning
confidence: 99%